2017
DOI: 10.1186/s12913-017-2573-9
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive qualitative examination of knowledge translation practice among health researchers in Manitoba, Canada

Abstract: BackgroundThe importance of effective translation of health research findings into action has been well recognized, but there is evidence to suggest that the practice of knowledge translation (KT) among health researchers is still evolving. Compared to research user stakeholders, researchers (knowledge producers) have been under-studied in this context. The goals of this study were to understand the experiences of health researchers in practicing KT in Manitoba, Canada, and identify their support needs to sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…To our knowledge, no similar review exists. In fact, researchers' KT practice has been described as understudied, yet, there is increased pressure for researchers to illustrate the policy and practice impact of their research [97][98][99]. This review reveals some efforts to document LMIC researchers' KT capacity, practice and efforts to enhance LMIC researchers' KT capacity and practice but also a need to strengthen the evidence base.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no similar review exists. In fact, researchers' KT practice has been described as understudied, yet, there is increased pressure for researchers to illustrate the policy and practice impact of their research [97][98][99]. This review reveals some efforts to document LMIC researchers' KT capacity, practice and efforts to enhance LMIC researchers' KT capacity and practice but also a need to strengthen the evidence base.…”
Section: Discussionmentioning
confidence: 99%
“…'Screening' shows the number of articles whose titles, abstracts and keywords were screened against the study inclusion and exclusion criteria (334) and the number of articles that were excluded at this stage (201). 'Eligibility' shows the number of full text articles that were screened against the inclusions and exclusion criteria (133) and the number of articles that were excluded at this stage (97). 'Inclusion' shows that number of articles that were included in the review (66), including those that met the inclusion criteria (36) and 30 articles identified from searching the reference lists of the 36 included articles.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…At least one survey study failed to find an association between researcher/knowledge user engagement and research utility [ 51 ], suggesting that the factors determining effective IKT have yet to be clearly identified. Knowledge of IKT among researchers varies [ 52 ], and there is limited evidence about how researchers and knowledge users should go about collaborating. Despite the slim evidence base, stakeholder enthusiasm for IKT continues to grow.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, acquiring knowledge translation skills in biological science education is critically important, particularly once undergraduates enter the workplace or continue their education (Graham et al, 2006). Moreover, the knowledge translation components of SL are viewed to be as essential as problem solving, critical thinking and collaborative skills (Wensing & Grol, 2019;Sibley et al, 2017). These findings demonstrate that students have attained proficiency in knowledge translation capabilities at the time of completing their undergraduate program.…”
Section: Discussionmentioning
confidence: 99%
“…Following the completion of an undergraduate degree in biological science, it is expected that graduates exhibit strong transferable skills in collaboration, critical thinking and problem-solving to ensure employment attainment and retention (Newton, Bettger, Buchholz, Kulak, & Racey, 2015;Wensing & Grol, 2019;Sibley, Roche, Bell, Temple & Wittmeier, 2017). To support these expectations, undergraduate teaching strategies should directly stimulate high-level skill development while simultaneously meeting course learning objectives (Newton et al, 2015).…”
Section: Introductionmentioning
confidence: 99%